MICROPROCESSING AND SOME IMMEDIATE OPPORTUNITIES FOR THE ENTREPRENEURIAL INFORMATION PROVIDER - MacKinnon, Ron; Pal, Gabrial (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF